Bicuspid Aortic Valve Prevalence In A Large Series Of Echocardiograms In The Area Of Frequent Consanguineous Marriage - Sucu, Murat; Davutoğlu, Vedat; Özer, Orhan; Başpınar, Osman; Aksoy, Mehmet; Kılıç, Metin (European Journal of Therapeutics, 2009)
Bicuspid aortic valve (BAV) is one of the most common congenital anomalies of the heart, though its definitive prevalence is not clear. We sought to determine the prevalence of BAV in a large database of echocardiographic measurements from a single institution in the area of frequent consanguineous marriage (South-east Anatolia region) and we present the frequencies of BAV-related complications such as stenosis, regurgitation, and assendan aorta dilatation. We retrospectively analyzed 31.265 echocardiograms performed at our academic institution between 2004 and 2007 for various indications. BAV is often associated with aortic stenosis, regurgitation, and ascending aorta dilatation and BAV is an independent risk factor for infective endocarditis. The prevalence of BAV was calculated, and the frequency of aortic stenosis, regurgitation, and ascending aorta dilatation among BAV cases was determined. Our database revealed a gender distribution of 11.339 males (47%) and 12.926 (53%) females.The total prevalence of BAV was 0.57% (n = 180). The rate of consanguineous marriage is 20.9% in overeall Turkey. The rate of consanguineous marriage is 40.4% in our region The gender-specific prevalence was 1.08% in males and 0.44% in females. Regurgitation was observed in 58.3% (28.9% mild, 29.4% severe) of BAV cases, stenosis in 40% (17.8% mild, 22.2% severe), and dilatation in 33.3%. The prevalence determined in our study is similar to the prevalence determined in other recent echocardiography and autopsy studies, suggesting a lower incidence of BAV than previously thought despite high rate of consanguineous marriage. Regurgitation was the most common valvular complication in our database.